Evaluation of Pricing Strategies of Elastic Traffic on a Single Communication Link - Peter Fodor; Adam Marquetant (Communications - Scientific letters of the University of Zilina, 2001)
The future integrated service networks supporting multiple traffic classes will require customized admission control and bandwidth sharing strategies, which meet the diverse needs of QoS (Quality of Service)-assured (stream) and best-effort (elastic) services. Recent research results indicate that it is meaningful to exercise call admission control (CAC) even for elastic (best-effort) traffic, because CAC algorithms provide a means to prevent e.g. TCP sessions from excessive throughput degradations [1], [2]. Based on a model of a single link introduced in [2], we evaluate different pricing strategies assigned to elastic calls by determining an optimal CAC using Markov Decision theory. We will show that optimizing CAC not only maximizes average revenue, but also improves blocking probability of high priority stream traffic and QoS of elastic traffic as long as appropriate pricing functions are applicable.